Consumer purchasing decisions of Somethinc products in Salatiga City: The influence of halal certification, online customer reviews, and celebrity endorsers through buying interest - Rahmawati, Defi Nur; Puspita, Rosana Eri (Nur Science Institute, 2024)
The beauty industry has recently developed very rapidly; currently, local beauty products are in great demand by the public, so various brands compete with each other to attract consumers; this impacts the sales of each product brand to be unstable. This article aims to analyze the effect of halal certification, online customer reviews, and celebrity endorsers on purchasing decisions and analyze the indirect influence of buying interest as a mediation variable. This type of research is quantitative, with a population of Salatiga City. The sampling technique used in this study is purposive sampling with 100 respondents. The analysis techniques used are statistical tests and path analysis. The results of statistical tests show that halal certification has no effect, while online customer reviews and celebrity endorsers influence purchasing decisions. Halal certification and online customer reviews do not affect buying interest, while celebrity endorsers affect buying interest. Purchase interest as a mediating variable cannot mediate halal certification and online customer review of purchasing decisions but can mediate celebrity endorsers against purchasing decisions. This study differs from other studies in adding a mediating variable, namely buying interest, to determine whether it can mediate an independent variable. Second, no studies have used three independent, dependent, and mediating variables simultaneously. Third, differences in location and time of study. Based on previous research, gap research needs to be reviewed again with added and different variables.